Luminescent MOF crystals embedded in PMMA/PDMS transparent films as effective NO2 gas sensors. Issue 6 (12th February 2020) - G. Moscoso, Francisco; Almeida, José; Sousaraei, Ahmad; Lopes-Costa, Tânia; Silva, Ana M. G.; Cabanillas-Gonzalez, Juan; Cunha-Silva, Luís; Pedrosa, José M.
Abstract : Transparent polymeric matrices serve as efficient platforms to immobilize Tb(BTC) crystals whose fluorescence is quenched in the presence of NO2 . Abstract : A fluorescent NO2 gas sensor using the metal–organic framework (MOF) Tb(BTC) (BTC = benzene-1, 3, 5-tricarboxylate) as an active material is reported here. The lanthanide MOF crystals have been immobilized in transparent films of two different inert and non-emissive polymers i.e. polymethylmethacrylate (PMMA) and polydimethylsiloxane (PDMS) by spin coating Tb(BTC) suspended in the corresponding polymer organic solution onto solid substrates. The presence of the MOF particles in the resulting fluorescent films has been further confirmed by SEM and optical microscopy images. The sensing films exhibit fast and sensitive responses (fluorescence quenching) when exposed to a low concentration of NO2 . The dependence of the sensor response on the analyte concentration fitted a two-site Stern–Volmer quenching model from which good calibration curves were obtained. These properties, along with recovery of the sensor emission after gentle heating (50 °C), make these materials realistic candidates for the development of luminescent sensing films based on MOFs.